As diversas faces do ensino médio : formar para a cidadania e/ou preparar para uma profissão - Furtado, Patrícia Lazzari (2012)
The present thesis, included in the Educational Policies research line, presents the theme of high school identity as a guide. The main goal is to analyze high school identity within the context of educational legislations and documents that regulate education functioning, in order to confront them with the type of formation high schools offer to today s youth. For this purpose we used, as methodology and documental analysis resources, the Federal Constitution of 1988, the Law of Directive and Bases (LDB) 9.394/96, the National Curricular Parameters for High School, the National Curricular Directives for High School, and the National Curricular Guidelines for High School. In this analysis, we systematically highlighted elements about the objective of high school institutions. After performing the characterization of High School identity in terms of legislation, the indication of some challenges which society needs to face so that high school can manage its role in basic education proceeds. The study performed allows to state that legislation clearly presents a high school identity, because, as identified in the LDB 9.394/96, article 35, the objective of high school is improving students as human beings, their ethic formation, the development of their intellectual and critical thinking autonomy, their preparation to the workplace, and the development of skills to ongoing learning. Then it is concluded that many challenges still hover over the matter of high school and that further studies are required, as documents present a high school identity, which in practice is submerged